Post-partum uterine involution and ovarian activity in suckled swamp buffalo - AHMED, K (The Indian Journal of Animal Reproduction, 2023)
Uterine involution and ovarian activity were monitored by per rectal palpation and oestrus detection from 3 to 5 daysto 180 days postpartum in 45 suckled swamp buffaloes maintained at Livestock Research Station, Mandira, Assam. Theinterval from parturition to regression of the corpus luteum (CL) of pregnancy and involution of uterus were I 0.13±0. 75 and30.80± 1.0 I days, respectively. During the first l 80 days post partum 35 (77. 78%) out of 45 suckling buffaloes were acyclic(anoestrus) and of IO animals (22.22%) exhibiting ovarian cycles of which 5(11.11%) were not detected in oestrus.
Keywords: Uterine involution; ovarian activity; post partum; buffalo